GAMIFIED LEARNING IN SPEAKING CLASS: INVESTIGATION OF OUTCOMES AND STUDENTS’ FEEDBACK AT TENTH GRADE STUDENTS OF SMAN 1 KOTA BENGKULU - Vera Dwi Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of game-based learning (gamified learning) on improving eighth-grade students' speaking skills in English lessons at SMAN 1 Bengkulu City and to determine students' perceptions of the method's implementation. This study used a mixed-methods approach by combining quantitative and qualitative data. Quantitative data were obtained through speaking tests (pre-test and post-test) and questionnaires with 20 Likert scale statements, while qualitative data were collected through semi-structured interviews and classroom observations. The pre-test results showed an average student score of 50.33 with a dominant category of "sufficient" (40%), while the post-test results increased significantly with an average of 84.00 and a dominant category of "very good" (50%). Descriptive statistical analysis also showed that all aspects of speaking skills improved, with the highest scores in the aspects of task completion (mean 4.47) and interaction engagement (mean 4.40). Observational results showed that the majority of students participated actively, focused, and enthusiastically, while interviews revealed that students felt more motivated, confident, and brave in speaking English through games. Thus, gamification learning has been proven to be effective in improving speaking skills while creating a fun learning atmosphere.